Methods of Population Estimation and Projection - Aryal, Gokarna Raj (Journal of Population and Development, 2020)
This research paper tries to clarify the differences between population estimation and projection. The main objective of this study is to introduce basic concept of population estimation and projection. It also explains the tools and techniques for estimation and projection of population in both regional and national levels. However, the perception of population estimation and projection is frequently confusing to the readers. Though the difference between the two is relatively normal and straightforward. Both concepts generate numbers that is intended to indicate the size of the population of a given geographical area at a specific point of time. Most of the developing countries, censuses are taken at every ten years' interval. Major changes of demographic events and features of the population are obtained for short periods. In this way, the foremost purpose of this study is to provide reliable and satisfactory projected data in both provincial and national levels. Various tools and techniques have been developed for estimation and projection of population i.e. mathematical, economic and cohort component. These techniques require accurate data and reliable information related to the fertility, mortality and migration of the country. In conclusion, the reliable projected data are vital for business and program planning, transparency, prosperity, policy discourse and good governance in different sectors of the nation for the upcoming days.